Predizendo impactos das mudanças climáticas sobre a diversidade funcional de peixes de água doce : um panorama "down under". - Oliveira, Anielly Galego de (2018)
The expected climate changes for the coming decades may accentuate the current massive loss of biodiversity. The effects on freshwater ecosystems can be further accentuated by changes in flow patterns, seasonality of flood events, and water quality. As important mediators of ecosystem functions in aquatic environments, we have the fishes. The distribution and abundance of the fish are affected by hydro-morphological, geological, physicochemical, biological and mainly climatic factors since they are ectothermic organisms. However, there is still no consensus as to which species would be most affected, from tropical regions to temperate regions because there is a gap in the knowledge of tropical, subtropical and temperate fish responses from the southern hemisphere to climate change. Thus, in order to find patterns in basin scale, this study aimed to predict, through the species distribution modeling, the effects of climate change on the distribution of freshwater fishes in two climatically distinct basins in the southern hemisphere, considering their effects on patterns of functional diversity. In addition, this study sought to identify areas of great conservation interest. The first approach evaluated the impacts of climate change on the subtropical climate of Paraná-Paraguay, in its taxonomic and functional component. The second approach evaluated the poor ichthyofauna of Murray-Darling, Australia, in face of climate change, inserting a physiological component of thermal tolerance of the species. Despite the marked differences between the basins, there was a similar trend in the results. The predictions indicated a marked loss in the range for all species and consequently for all functional traits. There was also a change in the species range, with a trend to seek higher places and/or higher latitudes. Several species can lose up to 100% of the climatically adequate areas, with possible extinction. Species predicted to be extinct are generally those with more specialized and frequent traits in the samplings. Despite the limitations of species distribution models, they may be essential in anticipating species responses to the impacts of climate change that can break the chain linking biodiversity, ecosystem processes and services, and human wellbeing.